2020
DOI: 10.1017/s1049023x20001387
|View full text |Cite
|
Sign up to set email alerts
|

All-Cause Hospitalizations after Large-Scale Hurricanes among Older Adults: A Self-Controlled Case Series Study

Abstract: Introduction: Understanding the drivers of health care utilization patterns following disasters can better support health planning. This study characterized all-cause hospitalizations among older Americans after eight large-scale hurricanes. Study Objective: The objective of this study was to characterize all-cause hospitalizations for any cause among older Americans in the 30 days after eight large-scale hurricanes. Methods: A self-controlled case series study among Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The excess risk for all-cause hospitalization associated with cyclone exposures was estimated by five studies from the United States. 9 , 56 , 63 65 Four of these studies observed an increased risk of all-cause hospitalization for up to 3 months after a high-amplitude hurricane (e.g., Hurricanes Katrina, Sandy, or Wilma). 9 , 56 , 63 , 65 A case-crossover study on eight large-scale hurricanes reported an elevated risk ranging from 15% to 37% for all-cause hospitalization among the population years of age in the 1-month period following cyclone exposures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The excess risk for all-cause hospitalization associated with cyclone exposures was estimated by five studies from the United States. 9 , 56 , 63 65 Four of these studies observed an increased risk of all-cause hospitalization for up to 3 months after a high-amplitude hurricane (e.g., Hurricanes Katrina, Sandy, or Wilma). 9 , 56 , 63 , 65 A case-crossover study on eight large-scale hurricanes reported an elevated risk ranging from 15% to 37% for all-cause hospitalization among the population years of age in the 1-month period following cyclone exposures.…”
Section: Resultsmentioning
confidence: 99%
“… 9 , 56 , 63 65 Four of these studies observed an increased risk of all-cause hospitalization for up to 3 months after a high-amplitude hurricane (e.g., Hurricanes Katrina, Sandy, or Wilma). 9 , 56 , 63 , 65 A case-crossover study on eight large-scale hurricanes reported an elevated risk ranging from 15% to 37% for all-cause hospitalization among the population years of age in the 1-month period following cyclone exposures. 63 However, another time-series study on Hurricane Sandy showed no change in inpatient use inside the storm zone but did show a statistically significant reduction outside the storm zone over the 1-y post-cyclone period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, the older adults (≥ 65) were more vulnerable than the young group during the typhoon. Bell found the sizeable increase in older inpatients during eight separate hurricanes of American [ 44 ]. Weinberder referred that the increase in the proportion of emergency department visits due to cardiovascular disease, respiratory disease and kidney disease among the older adults (≥ 65) was associated with Hurricane Sandy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%